Langerhans’ cell histiocytosis presenting as chronic otitis media a diagnostic dilemma (Indian Journal of Case Reports, 2025)
Langerhans’ cell histiocytosis (LCH) is a rare condition that can sometimes affect the temporal bone. When it involves the temporal bone, LCH may present with non-specific symptoms such as middle ear inflammation, ear pain, hard of hearing, external auditory canal polyps, or mastoid mucosal inflammation. In cases where patients show signs of chronic otitis media, LCH should be considered a possible differential diagnosis. This case report highlights a 38-year-old male patient who initially presented with features suggestive of chronic otitis media, was diagnosed to have LCH through histopathological analysis, and was treated according to medical oncology protocols.